2019
DOI: 10.1097/brs.0000000000002851
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Percutaneous Intradiscal Amniotic Suspension Allograft in a Rabbit Model of Intervertebral Disc Degeneration

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Other cell types were not further analyzed as only a limited number of studies utilized them. These included: fibroblast cells, 80 , 81 , 82 , 83 gynecological cells (menstrual blood derived stem cells and human amniotic cells), 84 , 85 hematopoietic stem cells, 77 hESC, 86 , 87 , 88 muscle derived stem cells, 89 olfactory stem cells, 90 and synovial derived mesenchymal stem cells. 91 , 92 Cellular therapies have been proposed either as cells alone or together with instructive biomaterials or growth factors to support regenerative properties.…”
Section: Proposed Cell Sources For Nucleus Pulposus Regenerationmentioning
confidence: 99%
“…Other cell types were not further analyzed as only a limited number of studies utilized them. These included: fibroblast cells, 80 , 81 , 82 , 83 gynecological cells (menstrual blood derived stem cells and human amniotic cells), 84 , 85 hematopoietic stem cells, 77 hESC, 86 , 87 , 88 muscle derived stem cells, 89 olfactory stem cells, 90 and synovial derived mesenchymal stem cells. 91 , 92 Cellular therapies have been proposed either as cells alone or together with instructive biomaterials or growth factors to support regenerative properties.…”
Section: Proposed Cell Sources For Nucleus Pulposus Regenerationmentioning
confidence: 99%
“…12 Luo et al have shown effective use of a single intradiscal injection of ASA in a rat annular puncture model to treat intervertebral disc degeneration by looking at maintenance of disc height on a radiograph, T-2 signal of the disc on magnetic resonance imaging and histologic sections after death. 13 In vitro studies from Flannery et al on an alternate lyophilized amnion-chorion and umbilical cord product (PTP-001) have shown that this product can cause a dose-dependent decrease in tumor necrosis factor and IL-1b in an inflammatory model and also shows anticatabolic effect through a dose-dependent decrease in MMP 13, a matrix metalloproteinase that degrades collagen. 14 These basic science studies show that proteins in these harvested and processed tissues are antiinflammatory, anticatabolic, and proanabolic and, therefore, seem to contain the "right stuff" to potentially treat chronic OA and tendinopathies in the future.…”
mentioning
confidence: 99%